Building therapeutic alliances with patients in treatment for low back pain: A focus group study. (5th November 2021) - Unsgaard‐Tøndel, Monica; Søderstrøm, Sylvia
Abstract: Background and Purpose: Low back pain is a multidimensional disorder and a biopsychosocial management approach is recommended. However, recent data indicates that physiotherapists mainly focus on biomechanical aspects in treatment and struggle with addressing psychosocial barriers for recovery. We wanted to explore how physiotherapists express their experiences of building therapeutic alliances within a biopsychosocial perspective of low back pain. Methods: Qualitative focus‐group interviews were performed with five physiotherapists on two occasions with 6 months in between. Data were analyzed within a hermeneutical perspective with decontextualization and recontextualization, and identification of themes. Results: Four main themes were identified from the analyses: (1) An ideal standard : Presence, empathy and applying the biopsychosocial perspective is central for building therapeutic alliance. (2) Time‐consuming : Active listening and personally adapted treatment is important and time‐consuming. (3) Challenging area : Advanced clinical reasoning is needed to understand and modify complex barriers for recovery. Clinical experience is sometimes necessary to integrate the psychological and social domains into physiotherapy management. (4) The art of balancing : Important to apply sensitive communication to help patients gain new insight. Some heavy psychosocial demands on patients may be outside physiotherapists' professional competence. Discussion: The physiotherapists in this focus group study expressed a shared view that therapeutic alliance should build upon person‐centering, motivational communication, and facilitation of lifestyle adjustments within a biopsychosocial perspective of low back pain. Complex clinical reasoning necessary as the optimal cause‐corrective treatment strategies were often not obvious. Time and tools to uncover and modify relevant psychological obstacles for recovery were perceived challenging and partly dependent on clinical experience. Addressment of psychosocial obstacles for recovery should be included in basic as well as postgraduate curriculums for physiotherapists. Collaborative practice support strategies like peer guidance and better platforms for interprofessional collaboration and decision support could contribute to improve practice in the psychosocial domain.